Exploring education preferences of Australian women regarding long-term health after hypertensive disorders of pregnancy: a qualitative perspective - Heike Roth; Amanda Henry; Lynne Roberts; Lisa Hanley; Caroline S. E. Homer (BMC, 2021)
Abstract Background Hypertensive disorders of pregnancy (HDP) affect 5-10% of pregnant women. Long-term health issues for these women include 2-3 times the risk of heart attacks, stroke and diabetes, starting within 10 years after pregnancy, making long-term health after HDP of major public health importance. Recent studies suggest this knowledge is not being transferred sufficiently to women and how best to transmit this information is not known. This study explored women's preferred content, format and access to education regarding long-term health after HDP. Methods This was a qualitative study and framework analysis was undertaken. Women with a history of HDP who had participated in a survey on long-term health after HDP were invited to participate in this study. During telephone interviews women were asked about preferences and priorities concerning knowledge acquisition around long-term health after HDP. Results Thirteen women were interviewed. They indicated that they wanted more detailed information about long-term and modifiable risk factors. Their preference was to receive risk counselling from their healthcare provider (HCP) early after giving birth along with evidence-based, print or web-based information to take home. All women suggested more structured postnatal follow-up, with automated reminders for key appointments. Automated reminders should detail rationale for follow-up, recommended tests and discussion topics to be addressed at the appointment. Conclusion Our findings show that most participants wanted information soon after birth with all women wanting information within 12 months post birth, complemented with detailed take-home evidence. Participants indicated preference for structured follow-up via their HCP with automated alerts about the appointment and recommended tests. This evidence can be used to guide the development of education programs for women on health after HDP which may enhance knowledge, preventive health management and more generally improve women's health trajectories.